The professionally oriented socio-cultural competence formation by means of the Internet use at foreign languages lessons - ROMANENKO, Oksana (Continuing Professional Education: Theory and Practice, 2019)
In the article the problem of future economists training for further professional activity is covered. It is underlined that the use of Internet intensifi es greatly the professional training of future specialists in economics. The key competences, the formation of which is the aim of foreign languages learning are defi ned. The importance of the role of professionally-oriented socio-cultural competence forming for students in economics is defi ned, the scopes of the use of Internet and information net functions are highlighted, the peculiarities of work with Internet-resources are given.